Persistence and viable but non-culturable state induced by streptomycin in Erwinia amylovora - Kim, Yeon Ju; Choi, Hyun Seo; Park, Duck Hwan (Frontiers in Microbiology, 2024)
Persister cell and viable but nonculturable (VBNC) state of bacteria are survival strategies against antibiotics and various environmental stresses, respectively, but they tend to be ignored in agriculture fields, even though bacteria can regain their abilities to survive and produce disease once those stresses disappear. This study was carried out to determine whether persister cell and VBNC state in Erwinia amylovora are present after exposures to streptomycin, the length of their persistence, and the steps needed to decrease the inoculum. Methods: Persister cells were observed using biphasic killed growth curve for 4-8 h when the late stationary phase cells of E. amylovora were cultured in liquid medium containing streptomycin. This state was maintained for up to 12 h based on the colony forming units (CFUs) of the colonies that grew on the mannitol glutamate yeast extract (MGY) medium after streptomycin was removed.Results: The CFUs on the MGY medium were lower than the total count determined using the LIVE/DEAD Kit, suggesting that persister cells and VBNC state might co-exist for up to 12 h after exposure to streptomycin. However, after 12 h, E. amylovora cells did not continue to grow on the medium for 9 days, suggesting that they entered a VBNC state at that time and remained in a persistent state. In addition, based on the Redox Sensor Green staining method, the presence of both states was confirmed for up to 12 h, and only then did the VBNC state became apparent. Furthermore, persister cells were observed for up to 24 h, and damaged cells reduced when E. amylovora cells were culture in distilled water with streptomycin, indicating that the uptake of lower nutrients in E. amylovora led to prolonged persister cells and VBNC state, which are more likely to survive after streptomycin treatments. The addition of sucrose and oxytetracycline to distilled water containing streptomycin reduced persister cells than other sources did. Conclusions: Thus, to inhibit the spread of fire blight, management techniques must consider the hazards of using streptomycin treatments that induce dormancy, such as persister cells and VBNC state, beyond the development of resistant strain.